Diverse metabolism of cell wall components of melting and non-melting peach genotypes during ripening after harvest or cold storage - Vasilakakis, Miltiadis; Diamantidis, Grigorios; Mignani, Ilaria; Manganaris, George A. (My University, 2006)
The mode of change in a range of physiological, physicochemical and biochemical parameters during fruit ripening between distinct peach genotypes (Prunus persica L. Batsch) after cold storage for up to 4 weeks was determined. The nectarine cultivar ‘Caldesi 2000’ was selected as a genotype with melting flesh (MF) characteristic (fruits characterized by extensive flesh softening during ripening) and the cultivar ‘Andross’ as a genotype with non-melting flesh (NMF) characteristic (fruits characterized by limited flesh softening during ripening). Flesh firmness, ethylene production, physicochemical and biochemical properties of the cell wall were determined and significant differences between the fruits of the two genotypes were recorded. Fruits of the NMF genotype were characterized by higher tissue retention and ethylene production during their ripening, higher content of uronic acids, as well as higher capacity for calcium binding in the water-insoluble pectin fraction compared with fruits of the MF genotype. Additionally, the ripening of MF-type fruits was characterized by higher losses of neutral sugars, especially those of arabinose and galactose than the NMF-type fruits and these losses were more intense after extended cold storage periods. In fruits of the NMF genotype the decreased activity of pectin methyl esterase (PME) combined with higher levels of calcium in the water-insoluble pectin fraction possibly provided less substrate for polygalacturonase (exo-, endo-PG) activity and less solubility of cell wall pectin compared with fruits of the MF genotype. Overall, the data indicate the existence of a wide range of diverse metabolic pathways during fruit ripening of fresh fruits withMF and NMF characteristics.
Keywords: Peach; Melting flesh; Non-melting flesh; Ripening; Cell wall; Pectin